Marmaduke Pickthall: a forgotten english novelist - Hasan, Md. Mahmudul (University of Portsmouth, UK, 2020)
It may be suggested that Marmaduke Pickthall’s political stance during WWI would not have ruined his literary reputation had the added factor of conversion to Islam not been present. Various anthologies have included selections from Pound’s poetry. We do not know when and if at all Pickthall would be immune to the politics of canon formation and be included in literary anthologies as a novelist and a travel writer. Pickthall’s absence from the canon and curriculum has deprived students and academics alike. The long overdue inclusion of his works in both will enrich English literature studies, delight the lovers of travel literature and “remedy a long period of neglect”.